A Four‐Electron Sulfur Electrode Hosting a Cu2+/Cu+ Redox Charge Carrier. (30th July 2019) - Wu, Xianyong; Markir, Aaron; Ma, Lu; Xu, Yunkai; Jiang, Heng; Leonard, Daniel P.; Shin, Woochul; Wu, Tianpin; Lu, Jun; Ji, Xiulei
Abstract: The elemental sulfur electrode with Cu 2+ as the charge carrier gives a four‐electron sulfur electrode reaction through the sequential conversion of S↔CuS↔Cu2 S. The Cu‐S redox‐ion electrode delivers a high specific capacity of 3044 mAh g −1 based on the sulfur mass or 609 mAh g −1 based on the mass of Cu2 S, the completely discharged product, and displays an unprecedently high potential of sulfur/metal sulfide reduction at 0.5 V vs. SHE. The Cu‐S electrode also exhibits an extremely low extent of polarization of 0.05 V and an outstanding cycle number of 1200 cycles retaining 72 % of the initial capacity at 12.5 A g −1 . The remarkable utility of this Cu‐S cathode is further demonstrated in a hybrid cell that employs an Zn metal anode and an anion‐exchange membrane as the separator, which yields an average cell discharge voltage of 1.15 V, the half‐cell specific energy of 547 Wh kg −1 based on the mass of the Cu2 S/carbon composite cathode, and stable cycling over 110 cycles. Abstract : Eine Schwefelelektrode mit Cu 2+ als Ladungsträger ergibt eine Vierelektronen‐Schwefelelektrodenreaktion durch die sequenzielle Konversion S⇌CuS⇌Cu2 S. Die Cu‐S‐Redoxionenelektrode hat eine hohe spezifische Kapazität von 3044 mAh g −1 bezogen auf Schwefel bzw. 609 mAh g −1 bezogen auf Cu2 S (das vollständig entladene Produkt) und zeigt ein beispiellos hohes Potential für die Schwefel/Metallsulfid‐Reaktion bei 0.5 V vs. SHE.